CLIMATE CHANGE AND FOOD SECURITY IN CENTRAL JAVA - Nadia Naja (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
Climate variability is one of the important challenges in the agricultural sector. Often the occurrence of climate anomalies is a limiting factor for agricultural activities. Precise climate predictions are very useful in developing strategies for planning activities and businesses in agriculture. The Impact of Climate Change on the Agricultural and Food Sector from the danger of drought is 241,682 Ha of land and 16,835 Ha of rice fields affected by drought with Potential Losses due to climate change in 2020-2024 of 11.18 trillion rupiah—food Availability Aspect, food security index. The food availability aspect has decreased from 88.88 in 2022 & 2023 to 87.69. This writing aims to find problems in climate change mitigation and adaptation policies and compile policy recommendations for food security in Central Java. The method used is SOAR Analysis (Strengths, Opportunity, Aspiration, and Result). Based on the SOAR Analysis, the variable of increasing the capacity of human resources of farmers and agricultural extension officers who are skilled and knowledgeable about climate data and information in high-value climate-adaptive agricultural practices was obtained. Policy options that the Central Java provincial government can consider are: (1) Increasing the budget for programs such as Climate Field Schools (SLI), Climate Smart Agriculture (CSA), and the Climate Village Program (PROKLIM), (2) Expanding the reach of farmer education and training programs to all districts/cities in Central Java, (3) Improving the quality of training materials with a focus on climate-adaptive agricultural practices, use of technology, and risk management (4) Developing assistance and mentoring programs for young farmers, (5) There needs to be regulations related to increasing the capacity of agricultural human resources at the provincial and district/city levels to collaboration on program funding to have budget efficiency and increase agricultural productivity.